Mengeksplorasi respon genotipe jagung calon hibrida umur genjah pada tekanan kepadatan populasi - Sulkifli; Hafizhah Al-Amanah; Eka Sudartik; Andi Cakra Yusuf; Hasriliandi Halim (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Research was conducted in an Experimental Farm to determine the response of several early maturing hybrid maize genotypes to population density pressure in Bone District, South Sulawesi Province, Indonesia. The experiment used a Split Plot Design consisting of main and subplots. The main plot consisted of four maize genotypes; ST201359 (Gt1), ST201312 (Gt2), Bima 7 (Gt3), Bima 3 (Gt4), and as subplots population density of 83,333 plants/ha (Pa), and 100,000 plants/ha (Pb). The two factors tested resulted in 8 treatment combinations, each combination was repeated three times as a block so that 24 experimental units were obtained. The results showed that maize genotypes Gt4, Gt1, Gt2, and Gt3, respectively, gave significant effects on almost all observed variables; plant height, flowering age, leaf area index, harvest age of maize genotypes < 90 hst, cob length, cob diameter, number of seeds per cob, yield per plot and yield per hectare. Population density pressure of 100,000 plants/ha as a single factor gave a significant effect on some of the observed variables namely; leaf area index, cob length, yield per plot, and yield per hectare increased with a population of 100,000 plants/ha. In this study, there was an interaction between maize genotype Gt4 (Bima 3) and population density of 100,000 plants/ha that significantly affected the variable of maize cob length.